2019
DOI: 10.12973/eu-jer.8.4.921
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison between the Fifth Grade Intensive English Language Curriculum and the Fifth Grade English Language Curriculum: Students’ Achievement in Speaking

Abstract: It is aimed, in this study, to compare the achievement level of the students taught with the fifth grade intensive English language curriculum (IELC) and the ones taught with the fifth grade English language curriculum (ELC) in terms of their speaking skills. With this aim, it is also intended to find out the failure behind the students' speaking skills. Sequential explanatory strategy, which is one of the mixed-methods research designs, was used for this study as the aim was to further explain the quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Erdem and Yücel-Toy (2017) also indicated that there were difficulties in speaking skill. Similarly, Kaya (2019) found in his study, which compared fifth grade students with and without foreign language oriented education, that despite the 15-hour language teaching per week, the students subjected to foreign language oriented education were not different than the students who were subject to 3 or 5 hours of language teaching per week in terms of speaking skills. In the same study, teachers also confirmed this situation and emphasized that there was always a deficiency in speaking skills, even though they did not experience any difficulties in developing other skills of the students.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Erdem and Yücel-Toy (2017) also indicated that there were difficulties in speaking skill. Similarly, Kaya (2019) found in his study, which compared fifth grade students with and without foreign language oriented education, that despite the 15-hour language teaching per week, the students subjected to foreign language oriented education were not different than the students who were subject to 3 or 5 hours of language teaching per week in terms of speaking skills. In the same study, teachers also confirmed this situation and emphasized that there was always a deficiency in speaking skills, even though they did not experience any difficulties in developing other skills of the students.…”
Section: Discussionmentioning
confidence: 67%
“…Seçkin (2011) indicated in their research that teachers stated that they could not reach enough explanations and examples regarding the activities. In addition, Kaya (2019) concluded that teachers had anxiety about associating with daily life and that they did not consider some of their practices sufficient. In this study, the inability of teachers to reach sufficient instructions about the activities may have reduced the overall effectiveness of the activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scholars from different theoretical schools and fields have begun to actively develop this problem. Interesting research has emerged on the targeted component of general and higher education (Ritchie Bates & Deary, 2015), models of critical thinking (Sadler, 2010), styles of thinking and perception of high school students (Kaya, 2019;Minchekar, 2017;Serin Serin, Saracaloglu & Ceylan, 2010), the role and relationship between critical thinking skills and learning outcomes of pupils/students (Ghazivakili et al, 2014;Sharma & Neetu, 2011).…”
Section: Introductionmentioning
confidence: 99%